2015
DOI: 10.1002/jbt.21729
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Boron on Arsenic-Induced Lipid Peroxidation and Antioxidant Status in Male and Female Rats

Abstract: The aim of the present study was to investigate the possible protective effects of boron, an antioxidant agent, against arsenic-induced oxidative stress in male and female rats. In total, 42 Wistar albino male and female rats were divided into three equal groups: The animals in the control group were given normal drinking water, the second group was given drinking water with 100 mg/L arsenic, and the third group was orally administered drinking water with 100 mg/kg boron together with arsenic. At the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 38 publications
0
10
0
3
Order By: Relevance
“…Consequently, sodium teeroborate inhibits chromium induced lipid peroxidation activity (antioxidant effect). It was reported that toxicity (oxidative stress) induced by vanadium 41 , titanium 29 , arsenic 42 can be prevented by addition of boron compounds. Recently, we have shown that boric acid when combined with oral administration with potassium dichromate inhibits the development of chromium-induced oxidative stress by inhibiting LPO and increasing the power of antioxidant status 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, sodium teeroborate inhibits chromium induced lipid peroxidation activity (antioxidant effect). It was reported that toxicity (oxidative stress) induced by vanadium 41 , titanium 29 , arsenic 42 can be prevented by addition of boron compounds. Recently, we have shown that boric acid when combined with oral administration with potassium dichromate inhibits the development of chromium-induced oxidative stress by inhibiting LPO and increasing the power of antioxidant status 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Canlılar için esansiyel bir eser element olan borun kimyasal form, doz ve maruziyet süresine bağlı olarak, antioksidan savunma mekanizmasını desteklediği, genotoksisite ve lipid peroksidasyona karşı potansiyel koruyucu etkileri olduğu, oksidatif stresi azalttığı rapor edilmiştir [14][15][16]. Yapılan çalışmalarda borun antioksidan savunmadaki rolünün yanı sıra, farklı kimyasal form ve dozlarda çeşitli kanser hücreleri için sitotoksik etki ile anti-proliferatif ve anti-kanserojen olduğu belirlenmiş, kanser gelişim riskini azaltabileceği için kanserden korunma amacı ile kullanılabileceği önerilmiştir [17][18][19][20][21].…”
Section: Sonuç Ve Yorumunclassified
“…Borun hücrelerde indirgenmiş glutatyon miktarını arttırdığı, oksidatif stresi ve buna bağlı olarak oluşabilecek oksidatif hasarı azalttığı çe-şitli kaynaklarda bildirilmektedir (7,32). İçme suyuna arsenik eklenen sıçanların kan ve dokularında, lipit peroksidasyon düzeyleri artarken, borik asit eklenmesi ile lipit peroksidasyonunun azaldığı rapor edilmiştir (33). Başka bir çalışmada ise tarım ilacı olarak çok sık kullanılan ve vücutta oksidatif stres oluşturan bir organofosfat olan malatyonun (malathione) toksisitesine maruz kalan sıçanlarda borun böbrek, karaciğer ve beyin dokuları ile kanda glutatyon düzeyini, süperoksit dismutaz ve katalaz aktivitesini arttırdığı gösterilmiştir.…”
Section: Deneysel çAlışmalarunclassified